2013
DOI: 10.1186/1471-2458-13-236
|View full text |Cite
|
Sign up to set email alerts
|

Exploring knowledge, attitudes and practices related to diabetes in Mongolia: a national population-based survey

Abstract: BackgroundNon-communicable diseases (NCDs) are now the leading causes of mortality in Mongolia, and diabetes, in particular, is a growing public health threat. Mongolia is a nation undergoing rapid and widespread epidemiological transition and urbanisation: a process that is expected to continue in coming decades and is likely to increase the diabetes burden. To better inform policy and public-health responses to the impact of the growth in NCDs, a national NCD Knowledge, Attitudes and Practices survey was imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 11 publications
8
47
1
2
Order By: Relevance
“…Just 15 % of the patients were in good conditions of diabetes nutrition knowledge. This result on knowledge is in accordance with the findings of studies carried out in other parts of Iran (12,13,17) and other countries (5,11,(18)(19)(20)(21)(22)(23). Niroomand et al reported high levels of patients' knowledge, attitude, and practice among Iranian diabetics in Alborz Province (10).…”
Section: Discussionsupporting
confidence: 88%
“…Just 15 % of the patients were in good conditions of diabetes nutrition knowledge. This result on knowledge is in accordance with the findings of studies carried out in other parts of Iran (12,13,17) and other countries (5,11,(18)(19)(20)(21)(22)(23). Niroomand et al reported high levels of patients' knowledge, attitude, and practice among Iranian diabetics in Alborz Province (10).…”
Section: Discussionsupporting
confidence: 88%
“…Na Mongólia, constatou-se que apenas uma em cada duas pessoas com DM2 estava ciente da progressão da doença e de suas complicações, e um terço delas desconhecia que o DM2 pode ser prevenido por meio de mudanças no estilo de vida, como por exemplo, a adesão a hábitos alimentares saudáveis e a realização de atividade física (18) . Considerando o tempo de diagnóstico da doença, é possível inferir que a não realização de atividades coletivas de educação para a saúde e o seguimento parcial das recomendações do Ministério da Saúde para o controle de doenças crônicas, referentes, por exemplo, à periodicidade de consultas médicas, de acordo com o grau de risco do doente, refletem nos resultados encontrados (19) .…”
Section: Discussionunclassified
“…Acredita-se que a ausência de sintomas ou desconforto podem levar as pessoas a não terem interesse em conhecer sua condição de saúde. Importante lembrar que as complicações da doença podem ser postergadas ou até mesmo evitadas quando os níveis glicêmicos são adequados, e estes são influenciados pelo controle de peso e outros comportamentos (17)(18) . Neste sentido, o conhecimento satisfatório sobre a doença pode ou não favorecer a atitude positiva com relação a ela.…”
Section: Discussionunclassified
“…Although the role of diet received 63.4% of adequate knowledge, only 26.9% and 20.1% of people knew that exercise and weight loss are key factors in prevention and treatment of type 2 DM [25].…”
Section: Discussionmentioning
confidence: 99%